IMPLEMENTATION OF THE TAHFIDZ QUR'AN PROGRAM AT THE DARUT TAUHID TANJUNGSARI-KREJENGAN ISLAMIC BOARDING SCHOOL - Umami, Lisa; Yunus, Moch.; Zaini, Bahruddin (Qawwam : The Leader's Writing, 2025)
This study aims to analyze the implementation of the Tahfidz Qur'an program at Pondok Pesantren Darut Tauhid Tanjungsari-Krejengan and to identify the supporting and inhibiting factors of its success. The main issues examined include how the program is carried out and the factors that influence its effectiveness. This research uses a descriptive qualitative approach with data collection techniques such as observation, in-depth interviews, and documentation. The findings reveal that the program is implemented systematically through structured memorization methods, and regular evaluations. Supporting factors include students' internal motivation, teacher competence, and a conducive environment. Meanwhile, inhibiting factors include limited time, students' busy schedules, and a lack of understanding of proper articulation (makharijul huruf) and tajweed. These findings are expected to contribute to improving the effectiveness of Tahfidz programs in Islamic boarding schools.